2015
DOI: 10.1097/aci.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

Innate responses to pollen allergens

Abstract: Purpose of review The aim of the present review was to discuss the effects of pollen components on innate immune responses. Recent findings Pollens contain numerous factors that can stimulate an innate immune response. These include intrinsic factors in pollens such as nicotinamide adenine dinucleotide phosphate oxidases, proteases, aqueous pollen proteins, lipids, and antigens. Each component stimulates innate immune response in a different manner. Pollen nicotinamide adenine dinucleotide phosphate oxidases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 91 publications
(120 reference statements)
0
38
0
1
Order By: Relevance
“…Pollens and other natural allergens are a complex mixture of proteases, antigens, lipids and oxidases. Proteases can not only damage cell junctions, increasing allergen penetration to dendritic cells, but also induce protease-activated receptor (PAR) signalling in epithelial cells [47]. Increased release of ROS by oxidases or mitochondria forms an important second hit, during this cascade, which is critical for sustained immune response.…”
Section: Mitochondrial Dysfunction and Allergymentioning
confidence: 99%
See 1 more Smart Citation
“…Pollens and other natural allergens are a complex mixture of proteases, antigens, lipids and oxidases. Proteases can not only damage cell junctions, increasing allergen penetration to dendritic cells, but also induce protease-activated receptor (PAR) signalling in epithelial cells [47]. Increased release of ROS by oxidases or mitochondria forms an important second hit, during this cascade, which is critical for sustained immune response.…”
Section: Mitochondrial Dysfunction and Allergymentioning
confidence: 99%
“…Such mice had greater IgE response with increased airway remodelling and hyperresponsiveness. The mechanistic connections between allergens and mitochondrial dysfunction may take one or more of many parallel paths [47]. Pollens and other natural allergens are a complex mixture of proteases, antigens, lipids and oxidases.…”
Section: Mitochondrial Dysfunction and Allergymentioning
confidence: 99%
“…Allergen challenge in subjects with asthma or seasonal allergic rhinitis has been reported to stimulate IL-8 secretion (2-4) and neutrophil recruitment (5) to the airways. Pollens contain numerous intrinsic factors that can stimulate an innate immune response (6). We and other have reported that intranasal challenge with pollen extract rapidly recruits neutrophils into the airways of naive mice (5,(7)(8)(9)(10).…”
Section: Clinical Relevancementioning
confidence: 99%
“…35,36 It has been shown that activated neutrophils accumulate at the site of allergic provocation and have the ability to prime CD4 + T cells, 37 a crucial event for the initiation of allergic inflammation. Grass pollen extract can induce neutrophil immune responses through the secretion of IL-8, 38,39 reinforcing the importance of this cytokine in the allergic response. We showed here that in TNF-α-stimulated lung epithelial cells, TGFβ1-mim suppressed IL-8 gene expression and cytokine secretion.…”
Section: Il-8 Is a Chemoattractant Cytokine Produced By A Variety Ofmentioning
confidence: 90%